Antioxidant Activity of Moringa oleifera Extracts - Wiwit Denny Fitriana; Taslim Ersam; Kuniyoshi Shimizu; Sri Fatmawati (Universitas Gadjah Mada, 2016)
Moringa oleifera have been evaluated for its antioxidant activity. M. oleifera leaves were extracted with methanol, ethyl acetate, dichloromethane and n-hexane. The antioxidant activity of extracts were evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity assay and an improved 2,2’-azino-bis-[3-ethylbenzothiazoline sulphonate] (ABTS) radical cation decolorization assay in vitro. Trolox was used as standard with IC50 5.89 μg/mL in DPPH assay and 3.06 μg/mL in ABTS assay. The methanol extract showed the highest free radical scavenging activity with IC50 value of 49.30 μg/mL in DPPH assay and 11.73 μg/mL in ABTS assay. This study provided that M. oleifera leaves possess antioxidant.